Modelling the Last Glacial Ice Sheet on Antarctica with Laterally Varying Relaxation Time - oude Egbrink, Dirk (author) (2017)
Glacial isostatic adjustment is the viscoelastic response of the earth to ice sheet loading. Ice dynamic models employ glacial isostatic adjustment to accurately simulate bedrock uplift. In previous studies, ice dynamic models use only a constant relaxation time to predict bedrock uplift. In this study, the aim is to improve an ice dynamic model by using a laterally varying bedrock relaxation time. Shear wave velocity data suggest a sharp increase in relaxation time between West and East Antarctica. Viscosity fields based on shear wave velocity data were converted to a set of relaxation time fields that are compatible with the ice dynamic model. These relaxation time fields were used in an ice dynamic simulation for the Antarctic Ice Sheet. It was found that largest differences between the different relaxation time models occur from 20 000 years ago up to PD. The model with a high relaxation time average showed a decrease in ice volume of 22.0%, whereas the model with a low relaxation time average, decreased by 17.4%. It was found that the largest differences between the models occurred at the WAIS due to the strong interaction of sea level and bedrock uplift. Furthermore, it was found that a reduction of ice sheet wavelength led to relaxation time decrease, locally up to 50%. This appeared to be a stabilising mechanism for decreasing ice sheets, but the effective retained ice volume by this mechanism remains unknown. Aerospace Engineering